Energy dissipation mechanisms in hollow metallic microlattices. Issue 16 (28th August 2014) - Salari-Sharif, Ladan; Schaedler, Tobias A.; Valdevit, Lorenzo
Abstract: Abstract : When properly designed at ultra-low density, hollow metallic microlattices can fully recover from compressive strains in excess of 50%, while dissipating a considerable portion of the elastic strain energy. This article investigates the physical mechanisms responsible for energy loss upon compressive cycling, and attributes the most significant contribution to a unique form of structural damping, whereby elastic local buckling of individual bars releases energy upon loading. Subsequently, a simple mechanical model is presented to capture the relationship between lattice geometry and structural damping. The model is used to optimize the microlattice geometry for maximum damping performance. The conclusions show that hollow metallic microlattices exhibit exceptionally large values of the damping figure of merit, (Young's modulus) 1/3 (loss coefficient)/(density), but this performance requires very low relative densities (<1%), thus limiting the amount of energy that can be dissipated.